Differences in correlates of energy balance in normal weight, overweight and obese adults. Issue 6 (November 2015) - Drenowatz, Clemens; Jakicic, John M.; Blair, Steven N.; Hand, Gregory A.
Summary: Purpose: The purpose of this study was to examine differences in total daily energy expenditure (TDEE), energy expenditure in various intensities, as well as total daily energy intake (TDEI) and diet quality in normal weight, overweight and obese men and women. Further, the association of energy expenditure and energy intake with body fatness was examined. Methods: The cross-sectional analysis included 430 adults (27.7 ± 3.8 years; 49.3% male). Body weight and height were measured according to standard procedures and percent body fat (BF) was assessed via dual X-ray absorptiometry. Energy expenditure was determined via the SenseWear Armband. Energy intake and the Healthy Eating Index (HEI) were calculated based on multiple 24-h recalls. Results: Weight adjusted TDEI and TDEE were significantly lower in overweight and obese adults compared to their normal weight peers ( p  < 0.001) and obese women had a lower HEI ( p  = 0.006). Overweight and obese adults further displayed a higher proportion of energy expenditure spent in sedentary and in light activities ( p  < 0.001), while the proportion of energy expenditure in moderate-to-vigorous physical activity (MVPA) was lower compared to their normal weight peers ( p  < 0.001). The inverse relationship between BMI or BF and MVPA was stronger than the positive association between BMI or BF and the proportion of energy expended in sedentary or light pursuits ( r MPA  = −0.45 to −0.67/ r MVPA  = −0.51 to −0.66 vs. r Sedentary  = 0.33 to 0.52/ r light  = 0.36 to 0.47; p  < 0.001). Conclusions: These findings emphasise the importance of MPA and bouts of MVPA regarding the maintenance of a normal body weight.